Risk factors for the development of interstitial lung disease following severe COVID-19 pneumonia and outcomes of systemic corticosteroid therapy: 3-month follow-up: Interstitial lung disease following severe COVID-19 pneumonia - Günay, Sibel; Parlak, Izzet Selcuk; Hezer, Habibe; Şeref Parlak, Ebru Şengül; Umut, Melike Sanem; Hancıoğlu, Zeynep; Çelenk Ergüden, Hülya; Kocaman, Yasin; Dalkıran, Aynil; Sertçelik, Ümran; Şerifoğlu, İrem and Akpınar, Esmehan and Göktaş, Muhammet Furkan and Fidan, Meltem and Babahanoğlu, Büşra and Cander, Fatma Sinem and Çıvgın, Esra and Er, Mükremin and Kılıç, Hatice and Argüder, Emine and Tuğ, Tuncer and Ünsal, Ebru and Hasanoğlu, Canan and Günay, İrem and Babayiğit, Muhammet and Ağca, Büşra and Karalezli, Ayşegül (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background: We aimed to evaluate the pulmonary involvement status, its related factors, and pulmonary function test (PFT) results in the first month follow-up in patients who were discharged for severe Covid-19 pneumonia, and to assess the efficacy of corticosteroid treatment on these parameters in severe pulmonary involvement patients. Methods: We retrospectively analyzed all consecutive patients who applied to our COVID-19 follow-up clinic at the end of the first month of hospital discharge. Functional and radiological differences were compared after 3 months of corticosteroid treatment in severe pulmonary involvement group. Results We analyzed 391 patients with “pulmonary parenchymal involvement” (PPIG) and 162 patients with “normal lung radiology” (NLRG). 122 patients in the PPIG (corticosteroid-required interstitial lung disease group (CRILD)) had severe pulmonary involvement with frequent symptoms and required corticosteroid prescription. Pulmonary involvement was more common in males and elder patients (P<0.001, for both). Being smoker and elderly were associated with a higher risk-ratio in predicting to be in PPIG (OR:2.250 and OR:1.057, respectively). Smokers, male and elderly patients, and HFNO2 support during hospitalization were risk factors for being a patient with CRILD (OR:2.737, OR:4.937, OR:4.756, and OR:2.872, respectively). After a three-months of methylprednisolone medication, a good response was achieved on radiological findings and PFT results in CRILD. Conclusions: In conclusion, after severe COVID-19 pneumonia, persistent clinical symptoms and pulmonary parenchymal involvement would be inevitable in elder and smoker patients. Moreover, corticosteroid treatment in patients with severe parenchymal involvement was found to be effective in the improvement of radiological and functional parameters.